Manajemen Operasi Internasional - Friska Fauziah Umardhi; Hendra Ibrahim (Jurnal Publikasi Ilmu Manajemen, 2025)
Operations management is a series of activities that a company uses to convert a variety of input ( raw materials, labor, etc.) into end products and services. Operations Management relates to the production of goods and services, and the output of the abundant production of Goods and Services is under the coordination and supervision of the operations manager. International operations management refers to the activities related to the transformation of an international company. Operations management is also closely linked to quality, productivity, and information technology. A company determines how input is transformed into goods or services. Correctly designed and operating systems are successful and procedures play a major role in determining product quality and productivity. The aim of this research is to find out how management on international operations. The method used is the library study method. This article is about managing international operations. Operations management is a series of activities that a company uses to convert a variety of input ( raw materials, labor, etc.) into end products and services. Operations Management relates to the production of goods and services, and the output of the abundant production of Goods and Services is under the coordination and supervision of the operations manager. The primary role of operations management is to create potential for achieving maximum value for the company. In other words, operation management is an activity to provide added value that is meant to create or add new value to the input of the organization in a way that directly affects the output.